Study of the removal of methylene blue from aqueous solution by using coir pith - Jeyanthi, Jeyanthi; Dhinakaran, Masilamai (Journal of Experimental Sciences, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> The use of reasonable and eco friendly adsorbents studied as an alternative substitution of activated carbon for removal of dyes from wastewater. Adsorbents prepared from coconut coir pith, which is a domestic waste, prosperously used to remove the methylene blue from an aqueous solution in a batch wise column. This study explores the potential use of coconut coir pith, pretreated with perfunctory treatment method, for removal of methylene blue from dye house wastewater. Treated coconut coir pith used to adsorb methylene blue at changing dye concentration, adsorbent dosage, pH and contact time. The sorption data were then correlated with the Freundlich and the langmuir adsorption isotherm models. In both isotherms exhibited a maximum K value in which indicates that the coir pith has greater affinity for methylene blue.